Prediction of discharge destination after traumatic brain injury in children using the head abbreviated injury scale. (16th April 2019) - Hubbard, Molly E.; Bin Zahid, Abdullah; Vonderhaar, Kathleen; Freeman, David; Nygaard, Rachel M.; Kiragu, Andrew; Guillaume, Daniel
ABSTRACT: Introduction : Traumatic brain injury (TBI) is a major public health problem, particularly in children. Prognostication of injury severity at the time of presentation is difficult. The Abbreviated Injury Scale (AIS) is a commonly used anatomical-based coding system created to classify and describe injury severity after initial presentation, once test results are able to better define the anatomical characteristics of the injury. We hypothesize that the Head AIS can predict discharge destination in children after TBI. Methods : The trauma registry database for a Pediatric Level 1 Trauma center was queried for patients age ≤14 years from 2006 to 2015 with a Head AIS>2. All diagnoses with head AIS>2 were retrieved. Since one patient can have multiple diagnoses with an AIS>2, we selected the diagnosis with highest Head AIS associated with each patient. The demographics, length of stay, and the discharge disposition of patients were retrieved. Descriptive statistics were performed and association of Head AIS with the length of stay and discharge disposition was determined using logistic regression. Results : 393 pediatric patients (age≤14 years) with an Head AIS ≥3, (64.0% males, mean age = 6.2 S.D. 4.58) presented over 10 years. Head AIS was strongly associated with mortality; with 0.8%, 1.1% and 42.0% of patients with Head AIS of 3, 4 and 5, respectively, dying – odds ratio for Head AIS 5 over Head AIS 3 = 89 (logistic regression, p-value<0.001). 80.0% of deaths (23 patients) in this cohort occurred within 24-h of presentation. Head AIS was associated with an increase likelihood of discharge to rehabilitation with 1.2%, 7.7% and 47.0% of survivors discharging to rehabilitation for Head AIS of 3, 4 and 5. Conclusion : Head AIS can reliably predict discharge disposition to home, rehab or death. Calculation of Head AIS prior to discharge could lead to accurate prediction of discharge destination.